2015
DOI: 10.1002/dvdy.24199
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling regulates dental papilla formation and tooth size during zebrafish odontogenesis

Abstract: Developmental Dynamics provides a focus for communication among developmental biologists who study the progressive and dynamic emergence of form and function during embryonic development. The journal is an international forum for the exchange of novel and substantive information on mechanisms that control development. We seek manuscripts presenting work done at all levels of biological organization, ranging from the molecular to the organismal, using both animal and plant model systems, and we welcome studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…GFP antibody labeling and alizarin red S staining of mineralized teeth was performed as in Yu et al (2015). We found that we could combine these two methods in a single specimen (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GFP antibody labeling and alizarin red S staining of mineralized teeth was performed as in Yu et al (2015). We found that we could combine these two methods in a single specimen (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Photographs of head and tooth GFP expression in living zebrafish embryos were taken with a Leica MZ16F stereoscope with a DCF300FX camera. For fixed tissue, to get a clear view of the tooth-forming region, the heart and yolk of embryos or larvae were manually removed with insect pins and the specimens were mounted ventral side up in glycerol under a small coverslip, as perviously described (Yu et al, 2015). Z-stacks for 3D image analysis were taken using either a Zeiss 510 Meta laser scanning confocal microscope, a Leica TCS SP8 confocal microscope, or a Zeiss Axio Imager M2 with an Apotome 2 structured illumination attachment.…”
Section: Methodsmentioning
confidence: 99%
“…Jackman et al [29] showed that, when Shha signaling is inhibited during the initiation stage, pitx2 expression is missing, indicating that Shha signaling is already crucial during very early stages. When inhibited at 36 hpf, further development of the dental mesenchyme and papilla is arrested with Shha inhibition at 48 hpf leader to dental hypoplasia [88].…”
Section: Tooth Development In Zebrafishmentioning
confidence: 99%
“…This special issue of Developmental Dynamics entitled “Organogenesis” illustrates the current state of our knowledge with respect to fundamental processes and pathways that govern organ development and homeostasis. A common theme in different tissues is the use of conserved signaling pathways such as FGF, Notch, TGFb, and Hedgehog that regulate organ primordia specification and differentiation in diverse tissues such as the liver (Wang et al, ), limb (Zhulyn and Hui, ), heart (Simmons et al, ), lung (Volckaert and De Langhe, ), tooth (Yu et al, in press), lymphatic and vascular systems (Secker and Harvey, ; Fish and Wythe, ), and the nervous system (Green et al, ). These signaling pathways often direct the tissue‐specific and cell‐type specific deployment of transcription factors (Harris et al, ; Islam et al, ; Pillai‐Kastoori et al, ; Praslicka and Gissendanner, ) and influence the activities of small and long noncoding RNAs (Nagalakshmi et al, ) that play critical roles in development.…”
mentioning
confidence: 99%